2004
DOI: 10.1042/bj20031785
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of histatin 5 and histatin 5-derived peptides with liposome membranes: surface effects, translocation and permeabilization

Abstract: A number of cationic antimicrobial peptides, among which are histatin 5 and the derived peptides dhvar4 and dhvar5, enter their target cells and interact with internal organelles. There still are questions about the mechanisms by which antimicrobial peptides translocate across the membrane. We used a liposome model to study membrane binding, translocation and membrane-perturbing capacities of histatin 5, dhvar4 and dhvar5. Despite the differences in amphipathic characters of these peptides, they bound equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…below MIC) can be attributed, at least initially, to electrostatics. Several studies investigating the interaction of cationic AMPs with model bacterial membranes have shown that an overcompensation in zeta potential at high peptide concentrations is associated with membrane insertion via hydrophobic interactions (22)(23)(24). A similar trend was also reported for the interaction of the cationic peptide rBPI 21 with LPS aggregates (24).…”
Section: Journal Of Biological Chemistry 27541supporting
confidence: 55%
“…below MIC) can be attributed, at least initially, to electrostatics. Several studies investigating the interaction of cationic AMPs with model bacterial membranes have shown that an overcompensation in zeta potential at high peptide concentrations is associated with membrane insertion via hydrophobic interactions (22)(23)(24). A similar trend was also reported for the interaction of the cationic peptide rBPI 21 with LPS aggregates (24).…”
Section: Journal Of Biological Chemistry 27541supporting
confidence: 55%
“…In a search for possible membrane-disturbing domains within the PV L2 protein, we observed similarity of a carboxyl-terminal L2 peptide with the synthetic peptide dhvar5 (LLLFLLKKRKKRKY) (Fig. 2A), which was recently shown to destabilize and depolarize membranes of bacteria and fungi, resulting in strong microbicidal and fungicidal activities (12). Peptide dhvar5 is a derivative of histatin 5, a human antimicrobial and antifungal peptide found in human saliva.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, would allow insight into the precise mechanism of peptide action. Using liposomes, it was recently shown for dhvar5 that negatively charged phospholipids are required for the peptide to translocate across and permeabilize membranes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Hst 5 is not a classical pore-or channel-forming peptide, since it has little disruptive activity in liposome model membranes (9) and cells treated with Hst 5 do not release dyes such as calcein (11). However, Hst 5 induces efflux of cellular ATP (20) and potassium and magnesium ions (42) and elevates cell permeability to small cationic dyes such as propidium iodide (40).…”
mentioning
confidence: 99%